Conductivity mechanism analysis at high temperature in bismuth titanate: A single crystal with sillenite-type structure - Lanfredi, S.; Nobre, MAL (American Institute of Physics (AIP), 2005)
Conductivity behavior of the Bi12TiO20 single crystal was investigated by the electric modulus spectroscopy, which was carried out in the frequency range from 5 Hz to 13 MHz and at temperatures higher than 400 degrees C. The resistance curve exhibits a set of properties correlated to a negative temperature coefficient thermistor. In the temperature range investigated, the characteristic parameter (,8) of the thermistor is equal to 4834 degrees C. Temperature coefficients of the resistance (a) were derived being equal to -3.02 x 10(-2) degrees C-1 at 400 degrees C and equal to -9.86 x 10(-3) degrees C-1 at 700 degrees C. The nature of the electric relaxation phenomenon and magnitude dc conductivity are approached. (c) 2005 American Institute of Physics.